Presupposition in The Mystery and Thriller Film of “Escape from Pretoria" - Haryati, Haryati (Journal of Pragmatics Research, 2022)
Presupposition itself has been a cause of the diversity of interpretations since presupposition sticks to utterances, sometimes unsaid clearly, that will provide implied meanings based on the context that is being talked about. The purposes of the study are to investigate three major points: the kinds of presupposition, their functions, and the percentage of each presupposition in the mystery and thriller film script of “Escape from Pretoria” by Francis Annan. This research used a qualitative method to analyze the obtained data. The observation is also used to collect data in which data are obtained from film scripts. The writer applies Yule’s theory (1996) to analyze the presupposition kinds, Halliday’s theory (2003) to analyze presupposition functions, and Subana’s formula to gain the percentage of each presupposition. As a result, there were 177 presuppositions obtained in the film script, with 166 existential presuppositions (93.8%), six factive presuppositions (3.4%), four lexical presuppositions (2.2%,) and one counterfactual presupposition (0.6%). From 177 presuppositions, the data were classified into 23 regulatory functions (13.0%), 2 interactional functions (1.1%), 57 representational functions (32.2%), 79 personal functions (44.6%), 1 imaginative function (0.6%), 4 instrumental functions (2.3%) and 11 heuristic functions (6.2%). Therefore, the dominant presupposition is existential, and the dominant function of presupposition is personal. Keywords: film script of Escape from Pretoria, pragmatics, presupposition